Strategi Marketing Public Relations dalam Meningkatkan Brand Awareness - Pritha Hanum Fahny; Maman Suherman (Bandung Conference Series: Public Relations, 2022)
Abstract. PT X Bandung is a Marketing Communication Agency, a company that helps business people/entrepreneurs in marketing their products or brands through digital media, such as websites, social media, email, and others. This company has been established for 9 years, with this company it will help several companies that have difficulty carrying out promotional activities, sales, and other marketing activities. This study discusses efforts to increase brand awareness of PT. X Bandung through Marketing Public Relations. In this study, the authors use qualitative research methods that are descriptive and tend to use analysis. In this study, the author uses the theoretical basis to focus the research in accordance with the facts on the ground. The data collection technique used is through interviews by holding meetings to conduct questions and answers with resource persons, in addition to conducting interviews, namely there are observations, literature studies and online data searches. The results of this study, PT Progo uses Company Profile as product information that will be conveyed to prospective customers through structured planning. Determine the communication media to convey existing product information, namely through face-to-face media. The problem that exists is the lack of trust from consumers so that the solution used is two-way communication to get criticism and suggestions from consumers. Determining the target target is with nominal budgeting and "like or dislike". Abstrak. PT X Bandung merupakan sebuah Marketing Communication Agency, perusahaan yang membantu para pebisnis/pengusaha dalam memasarkan produk atau brand mereka melalui media digital, seperti websiste, media sosial, email, dan lainnya. Perusahaan ini telah berdiri selama 9 tahun, dengan adanya perusahaan ini akan membantu beberapa perusahaan yang memiliki kesulitan melakukan kegiatan promosi, penjualan, dan kegiatan pemasaran lainnya. Penelitian ini membahas tentang upaya meningkatkan brand awareness PT. X Bandung melalui Marketing Public Relations. Dalam penelitian ini, penulis menggunakan metode penelitian kualitatif yang bersifat deksriptif dan cenderung menggunakan analisis. Dalam penelitian ini landasan teori dimanfaatkan penulis agar fokus penelitian sesuai dengan fakta di lapangan. Teknik pengumpulan data yang digunakan yaitu melalui wawancara dengan melakukan pertemuan untuk melakukan tanya jawab dengan narasumber, selain melakukan wawancara yaitu ada observasi, studi kepustakaan dan penelusuran data online. Hasil dari penelitian ini, PT Progo menggunakan Company Profile sebagai informasi produk yang akan disampaikan kepada calon konsumen dengan melalui perencanaan yang terstruktur. Menentukan media komunikasi untuk menyampaikan informasi produk yang ada yaitu dengan melalui media tatap muka. Permasalahan yang ada yaitu kurangnya kepercayaan dari konsumen sehingga solusi yang digunakan yaitu dengan komunikasi dua arah untuk mendapatkan kritik dan saran dari konsumen. Menentukan target sasaran yaitu dengan nominal budgeting dan “like or dislike”.